"¡No Pasarán!": Translators under siege and ideological control in the Spanish Civil War. (2nd January 2016) - Rodríguez-Espinosa, Marcos
Abstract : This paper traces the biographies of Paulina and Adelina Abramson, Irene Falcón, Maria Fortus, Ilse Kulcsar, Constancia de la Mora, Lise Ricol, and Lydia Kúper, a group of women who worked as translators during the Spanish Civil War. Before being appointed translators during this conflict, the professional training of some of them had been sponsored by the Red Army and the Comintern, the international communist organization created to spread, on a worldwide scale, the political changes of the Bolshevik Revolution. The Comintern recruited activists throughout the world, who eventually travelled to the USSR, where they received political indoctrination and sometimes linguistic training as translators. The Spanish Civil War was, for these translators, a unique opportunity to put translation at the service of 'the last great cause'. For most of them, the end of the Spanish conflict also meant the beginning of a long exile; not only due to the defeat of the Republic but also to their dissidence from Soviet orthodoxy. Some died far from their homelands, yet still had the chance to use translation as a weapon of resistance against General Franco; others were forced into a new exile after being exposed to the atrocities of Stalinism.